Correlation of Moisture, pH and Zeta Potential (z) in Sandy-Clay-Loam Soils of the Southern State of Hidalgo, Mexico - Prieto Mendez, Judith; Prieto Garcia, Francisco; Arturo Acevedo Sandoval, Otilio; Aurora Mendez Marzo, María (Asian Journal of Chemistry, 2014)
Agricultural soils in Savanna Zones are very sensitive to compaction and crusting, which merits investigation because, with respect to rainfall, crusting occurs in them and no matter how thin the crusts become to prevent infiltration and root development. The aim of this study was to determine a general correlation between parameters of moisture, pH and zeta potential (z). The last two parameters were measured in the saturation extract of three soil samples dedicated to the cultivation and production of malting barley (Hordeum distichum), in order to develop a rapid and simple method of estimating the quality of this type of soil. The stability of the colloidal suspensions of soils, associated with colloids of organic matter, is diminished dramatically (increasing the z), to the extent that it decreases the biological crust cover (% CC) and clay content which subsequently decreases the textural composition and, therefore the soil moisture retention capacity. Land plots in the municipality of E. Zapata, demonstrated the worst textural conditions (lower % age of clay), lower moisture content, the lowest organic matter loading, higher bulk density and lower field capacity. All these aspects confirm that plots in the southern region of the State of Hidalgo, Mexico consist of more compacted soils which are less beneficial for growing barley.